Amicum animal, sed magis amica veritas. “Estetica / arte animale”: alcune considerazioni critiche in prospettiva ermeneutica - Gurisatti, Giovanni (Scenari, 2024)
We adopt a disjunctive approach to the human-animal question, against the ethological conjunctive hypothesis that assimilates animal-human and animal-non-human. With Heidegger, we consider it necessary to distinguish the humanitas of man from both the anthropocentric humanism of the logocentric philosophical tradition and the zoobiocentric antihumanism of the bioevolutionary scientist tradition. We advocate an ontocentric ultrahumanism whereby man exclusively possesses the possibility to exceed his animal-being by virtue of a radical openness to the Other than himself. Only man can grasp the being “as such,” can give it aesthetic form and ethically let it be the being that it is. Only what flows from this free experience, neither functional nor utilitarian, can claim the name “art.” To speak of “art” in the case of animals is therefore simply nonsense. We thought it appropriate to raise some philosophical questions about the nonchalance with which the relationship between aesthetics, art and animality is taken for granted, for the sole purpose of fighting the specist and anthropocentric prejudice. We do not believe that aesthetic sensibility and artistic behavior have a single common animal root, implicit in biological life itself. Our thesis eschews all forms of anthropomorphizing animals and zoomorphizing humans, and for this very reason it is genuinely anti-anthropocentric and anti-speciesist.